INFECTIOUS DISEASES AND THEIR PREVENTION - Abdurazakova Iqbolkhan Abdurakhmonovna; Akhmadshoyev Rizvon Ruzmatjonovich (Web of Journals Publishing, 2023)
This article explores the significance of infectious diseases and the importance of their prevention. It discusses various methods, such as vaccination, hygiene, and public health measures, to curb the spread of infectious diseases. The article reviews recent literature and highlights the essential role of immunization in controlling diseases. It also discusses the methods and results of these prevention strategies, followed by a discussion of their implications for public health. The article concludes with suggestions for better preparedness in dealing with infectious diseases.
Keywords: Infectious diseases, prevention, vaccination, hygiene, public health, immunization, epidemiology, pathogen control, disease transmission, pandemic preparedness.